Nature’s Gallery – Collaborative and Adaptive Management for the Enhancement and Preservation of Natural Heritage - Antunović, Sara; Šikanja, Lorena; Troha, Gabriela (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
This paper is the result of an analysis of the tourist offer of the Petrinja Ceramics Studio and the Natura Education and Presentation Centre, which began with a site visit as part of student fieldwork and continued with further identification of problems through research of available information. The seasonality of visits, financial sustainability and the need to modernise certain programmes were identified as the main problems and challenges facing these facilities. This resulted in a problematic question: how to improve the tourist offer of Petrinja, taking into account its cultural and natural heritage? Therefore, this paper focuses on presenting proposals for improvements and development directions based on the principles of sustainability, active communities and appreciation of natural and cultural heritage. Considering the above, these two centres could become more recognisable and competitive in the tourism market by operating as the Nature's Gallery centre, which consists of a Natura Centre, a zoo, a souvenir shop, a ceramics studio and accommodation facilities.